Leaf surface-microstructure inspired fabrication of fish gelatin-based triboelectric nanogenerator. (May 2023) - Shi, Xuewen; Wei, Yuewen; Yan, Ren; Hu, Lixuan; Zhi, Jiacai; Tang, Biao; Li, Yijia; Yao, Zhuoqi; Shi, Chuanqian; Yu, Hai-Dong; Huang, Wei
Abstract: Triboelectric nanogenerators (TENGs) are promising for energy harvesting and self-powered sensing due to their small size, portability, and great potential to convert mechanical energy into electrical energy output. The structural design for the surfaces of friction pairs can efficiently improve the output performance of TENGs. However, current strategies for fabricating such surface structures are usually cumbersome, expensive, and/or eco-unfriendly. In this work, we report green fabrication of fish gelatin-based TENG (FG-TENG) inspired by the surface microstructures of natural leaves, which has low cost, superior performance, and good degradability. Leaves from four common plants with different microstructures were selected to modify the surface structures of friction pairs to achieve a performance gain in power generation. It is found that the friction pairs that mimics the pyramidal microstructures on the surface of the lotus leaf has the highest power generation performance. The voltage and current performance of leaf microstructure-inspired FG-TENG (LMFG-TENG) increases up to 5.8 and 3.8 times, with the maximum voltage of ∼320 V and the current of ∼0.80 μA. Furthermore, the LMFG-TENG exhibits excellent electrical stability, which can maintain electric output under ten thousand cyclic tests. Such LMFG-TENG has been not only used for energy harvest and power supply, but also used for self-powered sensing. This work provides a green and natural surface modification method of friction materials for enhancing the power generation of nanogenerators. Graphical Abstract: ga1 Highlights: Green fabrication of fish gelatin-based TENG (FG-TENG) inspired by the surface microstructures of natural leaves, which has low cost, superior performance, and good degradability. Leaves from four common plants with different microstructures were selected to modify the surface structures of friction pairs to achieve a performance gain in power generation. The LMFG-TENG that mimics the pyramidal microstructures on the surface of the lotus leaf has the highest power generation performance compared to other leaf structures. The LMFG-TENG was applied as a power supply device and a self-powered sensor for electrical powering and physical motion monitoring.